Analisis Pengaruh Variasi Diameter Puli terhadap Kualitas Telur dan Waktu Pada Proses Pengambilan Telur Burung Puyuh Secara Otomatis - Itok Maulana Firdayansyah; Arya Mahendra Sakti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the effect of pulley diameter variations on egg quality and collection time in an automatic conveyor system for quail (Coturnix coturnix japonica). The automatic system was designed to improve efficiency and maintain egg quality during the collection process. The experimental method used three pulley diameters: 22.1 mm, 24.7 mm, and 37.5 mm. The observed parameters included egg collection time and the rate of egg damage caused by mechanical vibration and belt tension. The results showed that pulley diameter significantly affects efficiency and egg quality. The 24.7 mm pulley produced the fastest collection time (31.66 s), while the 37.5 mm pulley resulted in the lowest damage rate (2.5%). The optimal pulley diameter range of 24.7–37.5 mm provides a balance between operational efficiency and egg quality.